Does childhood trauma moderate polygenic risk for depression?: a meta-analysis of 5765 subjects from the psychiatric genomics consortium - Peyrot, Wouter; Strohmaier, Jana; Rietschel, Marcella (Biological psychiatry, 2018)
Background The heterogeneity of genetic effects on major depressive disorder (MDD) may be partly attributable to moderation of genetic effects by environment, such as exposure to childhood trauma (CT). Indeed, previous findings in two independent cohorts showed evidence for interaction between polygenic risk scores (PRSs) and CT, albeit in opposing directions. This study aims to meta-analyze MDD-PRS × CT interaction results across these two and other cohorts, while applying more accurate PRSs based on a larger discovery sample. Methods Data were combined from 3024 MDD cases and 2741 control subjects from nine cohorts contributing to the MDD Working Group of the Psychiatric Genomics Consortium. MDD-PRS were based on a discovery sample of ∼110,000 independent individuals. CT was assessed as exposure to sexual or physical abuse during childhood. In a subset of 1957 cases and 2002 control subjects, a more detailed five-domain measure additionally included emotional abuse, physical neglect, and emotional neglect. Results MDD was associated with the MDD-PRS (odds ratio [OR] = 1.24, p = 3.6 × 10−5, R2 = 1.18%) and with CT (OR = 2.63, p = 3.5 × 10−18 and OR = 2.62, p = 1.4 ×10−5 for the two- and five-domain measures, respectively). No interaction was found between MDD-PRS and the two-domain and five-domain CT measure (OR = 1.00, p = .89 and OR = 1.05, p = .66). Conclusions No meta-analytic evidence for interaction between MDD-PRS and CT was found. This suggests that the previously reported interaction effects, although both statistically significant, can best be interpreted as chance findings. Further research is required, but this study suggests that the genetic heterogeneity of MDD is not attributable to genome-wide moderation of genetic effects by CT.
Published online: 21 September 2017
Gesehen am 16.08.2018